Formulasi dan Uji Aktivitas Antibakteri Sediaan Gel Ekstrak Daun Keji Beling (Sericocalyces crispus) Terhadap Bakteri Staphylococcus aureus dan Pseudomonas aeruginosa - vira Friska; Muahmmad Yunus; Razoki Razoki (Journal of Pharmaceutical and Sciences, 2026)
Skin infections caused by pathogenic bacteria such as Staphylococcus aureus and Pseudomonas aeruginosa remain a global health challenge, particularly due to the increasing incidence of antibiotic resistance. The development of topical formulations derived from natural products represents a potential alternative strategy. Keji beling leaves (Sericocalyces crispus) are known to contain secondary metabolites with antibacterial activity. This study aimed to formulate keji beling leaf extract into a gel preparation and evaluate its antibacterial activity. The 96% ethanol extract of keji beling leaves was obtained using the maceration method and subsequently formulated into gel preparations at extract concentrations of 5%, 10%, and 15% using hydroxypropyl methylcellulose (HPMC) as a gelling agent. The physical properties of the gels were evaluated through organoleptic, pH, and spreadability tests. Antibacterial activity against S. aureus and P. aeruginosa was assessed using the disc diffusion method by measuring the inhibition zone diameter. The results showed that all gel formulations exhibited good physical characteristics, with pH values ranging from 4.44 to 5.71 and spreadability within the acceptable range for topical preparations. The gel preparations demonstrated antibacterial activity against both test bacteria, with inhibition zone diameters increasing in proportion to the extract concentration. The formulation containing 15% extract exhibited the highest antibacterial activity (mean inhibition zone diameter of 9.50 mm against P. aeruginosa), although it remained lower than that of the positive control. In conclusion, keji beling leaf extract gel possesses favorable physical characteristics and shows potential for further development as a natural-based topical antibacterial agent, particularly at a concentration of 15%.